Istri yang Bekerja dalam Perspektif Al-Quran Studi Penafsiran M. Quraish Shihab terhadap Kata Qawwam dalam QS. An-Nisa/4:34 dan Penafsiran QS. Al-Ahzab/33:33 - Rahma, Nur Fadhillah (Lembaga Yasin AlSys, 2024)
Nowadays, in households, very large and urgent economic needs often become a problem in the household, making the wife play a role in meeting daily needs. Moreover, nowadays, where the price of goods and the cost of living are getting higher and higher, making the wife have no other choice but to look for work outside the home, even though her